PENERAPAN SISTEM INFORMASI DAN ALAT PRODUKSI SERTA PEMASARAN GUNA MENINGKATKAN PRODUKTIVITAS PRODUK PADA SERIKAT SAHABAT SAMBAT - Sharazita Dyah Anggita; Ikmah Ikmah; Fitri Juniwati Ayuningtyas; Muhammad Eko Mahfudin; Yudith Risdani; Fatkhul Ulum (Universitas Mataram, 2025)
Nanti Kita Sambat Tentang Hari Ini (NKSTHI) is a social media platform that develops a merchandise store called Sumber Sambat. Several problems remain unresolved in the business process, including the lack of an inventory management information system, the production process still relies on third parties, and product photography continues to rely on natural light, which is hindered by weather conditions. Based on the background and discussion above, this Community Partnership Program will be implemented to address data management and production issues at Sumber Sambat. This program is implemented through the use of an inventory management information system to enhance the efficiency and accuracy of production data. Additionally, the optimisation of production equipment is carried out to expedite the work process and reduce dependence on third parties in fulfilling product demand. Procurement of product photography lighting equipment is also carried out to expedite the work process and enhance the quality of visual marketing. The results of the activity demonstrate increased efficiency through the implementation of a management information system, as measured by the System Usability Scale (SUS), with a value of 70.625, which falls within the